2017
DOI: 10.1007/s10853-017-0973-1
|View full text |Cite
|
Sign up to set email alerts
|

Large pyroelectric properties at reduced depolarization temperature in A-site nonstoichiometry composition of lead-free 0.94Na x Bi y TiO3–0.06Ba z TiO3 ceramics

Abstract: Nonstoichiometry lead-free 0.94Na x Bi y TiO 3 -0.06Ba z TiO 3 (N x B y T-0.06B z T) (from x = y = 0.5, z = 1.00 to x = 0.5, y = 0.534, z = 1.02) ceramic compositions were prepared by a conventional solid-state route. XRD shows that the compositions are at a morphotropic phase boundary where rhombohedral and tetragonal phases coexist. The depolarization temperature (T d ) can be lowered by modifying x, y and z. The pyroelectric coefficient (p) of nonstoichiometry N x B y T-0.06B z T compositions is greatly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…), and energy harvesting efficiency (F e = p 2 /ε r ε 0 ), where C v denotes the volume heat capacity, ε 0 denotes the vacuum permittivity (ε 0 = 8.854 × 10 −12 F/m), ε r denotes the relative permittivity, and tan δ denotes the dielectric loss. 8,44,45 7E, the room-temperature pyroelectric coefficient of x = 0.05 is the largest among the reported niobatebased ceramics. In addition, the FOMs of x = 0.05 are also comparable or higher than those of several lead-free and lead-based ceramic materials.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…), and energy harvesting efficiency (F e = p 2 /ε r ε 0 ), where C v denotes the volume heat capacity, ε 0 denotes the vacuum permittivity (ε 0 = 8.854 × 10 −12 F/m), ε r denotes the relative permittivity, and tan δ denotes the dielectric loss. 8,44,45 7E, the room-temperature pyroelectric coefficient of x = 0.05 is the largest among the reported niobatebased ceramics. In addition, the FOMs of x = 0.05 are also comparable or higher than those of several lead-free and lead-based ceramic materials.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to the pyroelectric coefficient, FOMs were used to evaluate the pyroelectric properties of ferroelectric materials. FOMs include the current detectivity ( F i = p / C v ), voltage detectivity ( F v = p / C v ε r ε 0 ), detectivity ( F d = p / C v ( ε r ε 0 tan δ ) 1/2 ), and energy harvesting efficiency ( F e = p 2 / ε r ε 0 ), where C v denotes the volume heat capacity, ε 0 denotes the vacuum permittivity ( ε 0 = 8.854 × 10 −12 F/m), ε r denotes the relative permittivity, and tan δ denotes the dielectric loss 8,44,45 . F i , F v , and F d are used in charging the fast pulse, large area, and pyroelectric point detectors, respectively 44 .…”
Section: Resultsmentioning
confidence: 99%
“…Abe et al investigated MnO 2 -doped NBT-6BT and reported p = 3.5 × 10 −4 C m −2 K −1 at room temperature [ 23 ]. Recently, Balakat et al have been extensively investigating the pyroelectric properties of 0.94Na x Bi y TiO 3 -0.06Ba z TiO 3 [ 24 ], 0.94Na 1/2 Bi 1/2 TiO 3 -0.06Ba 1+x TiO 3 [ 25 ], La-doped NBT-6BT [ 26 ], Ta-doped NBT-6BT [ 27 ], and La, Ta-doped NBT-6BT [ 28 ]. The depolarization temperature (T d ) is lowered using these doping strategies; however, only a small improvement was observed in the pyroelectric figures of merit (FOMs).…”
Section: Introductionmentioning
confidence: 99%
“…(1− x )BNT– x Ba(Zr,Ti)O 3 system with x = 0.06‐0.07 near MPB was reported to exhibit large p of 5.7 × 10 −8 Ccm −2 K −1 . Moreover, the p of BNT–BT ceramics can be significantly enhanced from 3.15 × 10 −8 to 6.99 × 10 −8 Ccm −2 K −1 through a modulation of Na + /Bi 3+ molar ratio . Doping with elements such as Ba, Mn, and La is another effective way to improve the pyroelectric properties.…”
Section: Introductionmentioning
confidence: 99%
“…23 Moreover, the p of BNT-BT ceramics can be significantly enhanced from 3.15 9 10 À8 to 6.99 9 10 À8 Ccm À2 K À1 through a modulation of Na + /Bi 3+ molar ratio. 24 Doping with elements such as Ba, 25 Mn, 26 and La 27 is another effective way to improve the pyroelectric properties. Recently, a rather high p of 7.42 9 10 À8 Ccm À2 K À1 in BNT-BT ceramics was achieved by Balakt et al through La doping.…”
Section: Introductionmentioning
confidence: 99%